How does the green insurance policy affect the performance of heavy-polluting enterprises: an empirical study based on Chinese listed companies - Xin-Guang, Li; Shi-Zheng, Zhang; Wen-Yu, Wang; Yu-Dong, Weng; Nan-Nan, Cao (Frontiers in Environmental Science, 2025)
This study takes the implementation of the “Guiding Opinions on Launching Pilot Programs for Mandatory green Insurance” in 2013 as a quasi-natural experiment. Based on the panel data of A-share listed companies from 2008 to 2023, it systematically examines the impact of the green insurance policy on the performance of heavy-polluting enterprises by using the difference-in-differences (DID) method. The research findings show that the green insurance policy significantly improves the performance level of heavy-polluting enterprises. Mechanism tests indicate that the green insurance promotes the improvement of corporate performance through two paths: incentivizing enterprises’ technological innovation and enhancing their short-term debt financing capacity. Further heterogeneity analysis reveals that the policy has a more prominent role in improving the performance of enterprises with lower environmental investment levels, non-state-owned nature, and less financing constraints. The test of moderating effects finds that the board size negatively moderates the promoting effect of the green insurance on corporate performance, while the proportion of independent directors exerts a positive moderating effect. This study provides theoretical support and empirical evidence for the optimal design of the green insurance policy and the green and low-carbon transformation of heavy-polluting enterprises, and has important implications for improving the green insurance system and serving the high-quality development of the economy.